The Landscape of Obesity Education Worldwide — Are We Doing Enough? Scoping Review of Content of Obesity Educational Interventions in Medical Schools and Residency Programs - Wahiba Elhag (5245547) (2025)
No study appraised the curricular content of published obesity education interventions (OEI) delivered to medical students, residents, or fellows. This scoping review identified and described the curricular content of published OEI, examined the specific obesity-related domains addressed, and proposed potential directions for future intervention development. We searched PubMed and Web of Science databases. Original articles on OEI delivered to medical students, residents, or fellows were included. Data extraction was guided by the Obesity Medicine Education Collaborative’s framework and the Accreditation Council for Graduate Medical Education-International (ACGME-I) competencies framework. The curricular content of OEI was categorized and visually mapped to identify trends and gaps. A total of 490 studies were identified, and 60 were included. Conceptually, twelve obesity domains emerged: epidemiology, health policy, prevention; basic sciences; nutrition; physical activity; behavioral aspects; counseling; pharmacotherapy; metabolic/bariatric surgery (MBS); weight stigma; ethics/professionalism; health literacy; and practice guidelines. Geographically, most OEI (88.3%) were implemented in North America. Three-quarters of OEI were for medical students, less OEI were for residents, and none for fellows. Content-wise, the OEI for medical students and for residents exhibited strikingly limited coverage of all obesity domains, although those for residency programs had more limited coverage than those for medical schools. Across medical schools, the most common domains addressed were basic sciences (48.3%), counseling, and nutrition (45% each); the least included were pharmacotherapy (13.3%), ethics/professionalism (3.3%), and health literacy (1.6%). For residency programs, the most common domains addressed were basic sciences and counseling (21.6% for each); the least were pharmacotherapy and MBS (6.6% each), weight stigma (5%), ethics/professionalism (3.3%) and health literacy (1.6%). Many critical domains of obesity remain inadequately addressed in the education provided in medical schools and residency programs. Future OEI should incorporate these to equip future physicians with knowledge, skills, and attitudes to care for patients with obesity. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11695-024-07654-y